2000
DOI: 10.1105/tpc.12.10.1903
|View full text |Cite
|
Sign up to set email alerts
|

AHM1, a Novel Type of Nuclear Matrix–Localized, MAR Binding Protein with a Single AT Hook and a J Domain–Homologous Region

Abstract: Interactions between the nuclear matrix and special regions of chromosomal DNA called matrix attachment regions (MARs) have been implicated in various nuclear functions. We have identified a novel protein from wheat, AT hookcontaining MAR binding protein1 (AHM1), that binds preferentially to MARs. A multidomain protein, AHM1 has the special combination of a J domain-homologous region and a Zn finger-like motif (a J-Z array) and an AT hook. For MAR binding, the AT hook at the C terminus was essential, and an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 69 publications
0
16
0
1
Order By: Relevance
“…Single AT‐hook domain containing proteins such as SOB3 and ESC are hypothesized to bind DNA, and associate with the nuclear matrix (Fujimoto et al. , 2004; Morisawa et al. , 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single AT‐hook domain containing proteins such as SOB3 and ESC are hypothesized to bind DNA, and associate with the nuclear matrix (Fujimoto et al. , 2004; Morisawa et al. , 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The rice HMGA protein, PF1, is able to bind and enhance the activity of the rice PHYA promoter, suggesting a gene regulatory role for AT-hook proteins in photomorphogenesis (Martinez-Garcia and Quail, 1999). Single AT-hook domain containing proteins such as SOB3 and ESC are hypothesized to bind DNA, and associate with the nuclear matrix (Fujimoto et al, 2004;Morisawa et al, 2000). A SOB3/ ESC family member, AHL1, is suggested to encode a nuclear localized matrix attachment region (MAR) protein (Fujimoto et al, 2004).…”
Section: Sob3 and Esc Are Involved In Seedling Developmentmentioning
confidence: 99%
“…Furthermore, it can affect transcription of a large number of genes, as we demonstrated by microarray analysis. Studies on AT‐hook proteins in wheat ( Triticum aestivum ) ( AHM1 , Morisawa et al. , 2000) and Arabidopsis ( AHL1 , Fujimoto et al.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it can affect transcription of a large number of genes, as we demonstrated by microarray analysis. Studies on AT-hook proteins in wheat (Triticum aestivum) (AHM1, Morisawa et al, 2000) and Arabidopsis (AHL1, Fujimoto et al, 2004) have revealed that they can bind to the matrix attachment region (MAR) and are localized to the nuclear matrix, suggesting that they can function as a nuclear matrix component. ORE7/ESC appears to be paralogous to AHL1 with a similarity in sequence and protein size.…”
Section: Discussionmentioning
confidence: 99%
“…AHM1 and AHL1 are two other nuclear matrix-localized and MAR-binding proteins that contain a single AT hook and a J domain-homologous region or plant and prokaryote conserved (PPC) domain. These proteins function between the intranuclear framework and MARs by recruiting specific partners as co-chaperones (Fujimoto et al, 2004;Morisawa et al, 2000). Other MAR-binding proteins, such as MARBP-1 and MARBP-2, may have multifunctional roles in chromatin organization and ribosome biogenesis (Hatton and Gray, 1999).…”
Section: Introductionmentioning
confidence: 99%